2003
DOI: 10.1254/jphs.93.430
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Human Organic Anion Transporters in the Choroid Plexus and Their Interactions With Neurotransmitter Metabolites

Abstract: Abstract. The purpose of the present study was to elucidate the expression of human organic anion transporter 1 (hOAT1) and hOAT3 in the choroid plexus of the human brain and their interactions with neurotransmitter metabolites using stable cell lines. Immunohistochemical analysis revealed that hOAT1 and hOAT3 are expressed in the cytoplasmic membrane and cytoplasm of human choroid plexus. Neurotransmitter metabolites, namely, 5-methoxyindole-3-acetic acid (5-MI-3-AA), homovanillic acid (HVA), vanilmandelic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(56 citation statements)
references
References 29 publications
1
53
1
1
Order By: Relevance
“…In this regard, we found that hOAT3 mRNA is expressed in the brain (34), and the localization of hOAT1 in the blood-brain barrier was recently confirmed immunohistochemically (35). In the current study, we revealed that hOAT1 and hOAT3 mediates the transport of aflatoxin B1.…”
Section: Discussionsupporting
confidence: 66%
“…In this regard, we found that hOAT3 mRNA is expressed in the brain (34), and the localization of hOAT1 in the blood-brain barrier was recently confirmed immunohistochemically (35). In the current study, we revealed that hOAT1 and hOAT3 mediates the transport of aflatoxin B1.…”
Section: Discussionsupporting
confidence: 66%
“…In the present study, we report on the capability of OATs to transport GA derivatives across membranes. Since these transporters are present also in the brain [18], OATs may not only influence plasma levels of GA derivatives by securing their renal excretion but may also have an important impact on their levels in brain tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these are highly expressed in the kidneys (OAT1-OAT4, Oat5, Oat v 1, and URAT1), whereas Oat6 is only expressed in the olfactory bulb, and the recently identified human OAT7 is currently the only liver-specific OAT. The substrate panel of OATs includes important endogenous compounds like urate (15)(16)(17), prostaglandins (18), neurotransmitter and tryptophan metabolites (19,20), sulfated steroids, and a long list of drugs such as anti-viral drugs, antibiotics, antidotes (21), or diuretics (22)(23)(24).…”
mentioning
confidence: 99%